Delayed enhancement cardiac computed tomography for the assessment of myocardial infarction: From bench to bedside - Rodriguez Granillo, Gaston Alfredo (2017)
A large number of studies support the increasingly relevant prognostic value of the presence and extent of delayed enhancement (DE), a surrogate marker of fibrosis, in diverse etiologies. Gadolinium and iodinated based contrast agents share similar kinetics, thus leading to comparable myocardial characterization with cardiac magnetic resonance (CMR) and cardiac computed tomography (CT) at both first-pass perfusion and DE imaging. We review the available evidence of DE imaging for the assessment of myocardial infarction (MI) using cardiac CT (CTDE), from animal to clinical studies, and from 16-slice CT to dual-energy CT systems (DECT). Although both CMR and gadolinium agents have been originally deemed innocuous, a number of concerns (though inconclusive and very rare) have been recently issued regarding safety issues, including DNA double-strand breaks related to CMR, and gadolinium-associated nephrogenic systemic fibrosis and deposition in the skin and certain brain structures. These concerns have to be considered in the context of non-negligible rates of claustrophobia, increasing rates of patients with implantable cardiac devices, and a number of logistic drawbacks compared with CTDE, such as higher costs, longer scanning times, and difficulties to scan patients with impaired breath-holding capabilities. Overall, these issues might encourage the role of CTDE as an alternative for DE-CMR in selected populations.